Cardiac autonomic activity and blood pressure among Nunavik Inuit adults exposed to environmental mercury: a cross-sectional study - Poirier Paul; Dewailly Eric; Valera Beatriz (BMC, 2008)
Abstract Background Mercury is a contaminant that reaches high levels in Nunavik (North of Quebec). It is transformed into methylmercury (MeHg) and accumulated in marine mammals and predator fish, an important part of the traditional Inuit diet. MeHg has been suggested to affect BP in adults and children while the influence on HRV has only been studied in children. We aimed to assess the impact of MeHg levels on HRV and BP in Inuit adults from Nunavik. Methods In the fall of 2004, the «Qanuippitaa?» Health Survey was conducted in Nunavik (Quebec, Canada) and information on HRV was collected among 280 adults aged 40 years and older. Indicators of the time and frequency domains of HRV were derived from a 2-hour Holter recording. BP was measured according to the Canadian Coalition for High Blood Pressure technique. Pulse pressure (PP) was the difference between systolic (SBP) and diastolic blood pressure (DBP). Blood mercury concentration was used as exposure biomarker. Statistical analysis was conducted through linear regression and multivariable linear regression was used to control for confounders. Results Mercury was negatively correlated with low frequency (LF) (r = -0.18; p = 0.02), the standard deviation of RR intervals (SDNN) (r = -0.14; p = 0.047) and the coefficient of variation of RR intervals (CVRR) (r = -0.18; p = 0.011) while correlations with other HRV parameters did not reach statistical significance. After adjusting for confounders, the association with LF (beta = -0.006; p = 0.93) became non significant. However, the association with SDANN became statistically significant (beta = -0.086; p = 0.026) and CVRR tended to decrease with blood mercury concentrations (beta = -0.057; p = 0.056). Mercury was positively correlated with SBP (r = 0.25; p < 0.0001) and PP (r = 0.33; p < 0.0001). After adjusting for confounders, these associations remained statistically significant (beta SBP = 4.77; p = 0.01 and beta PP = 3.40; p = 0.0036). Moreover, most of the HRV parameters correlated well with BP although SBP the best before adjustment for mercury exposure. Conclusion The results of this study suggest a deleterious impact of mercury on BP and HRV in adults. SBP and PP increased with blood mercury concentrations while SDANN decreased with blood mercury concentrations.